Overview and analysis of the Department of Defense Discovery Metadata Specification (DDMS) how the DoD is using metadata to make its massive data stores more visible. - Sick, Michael (SOA webservices journal.)
The Department of Defense (DoD) Discovery Metadata Specification (DDMS) describes the DOD's preferred approach for decorating data assets with metadata. By providing a common convention for metadata, the DoD is building a common system for asset discovery, search, description, consumption and security. This article provides a summary of the DDMS's purpose, structure and capability. Upon completion the reader should have a basic understanding of the DDMS and should know where to go to get more detail and related materials. All questions regarding this article should be directed to Michael Sick at mike@serenesoftware.com